1997
DOI: 10.1007/s11661-997-0149-8
|View full text |Cite
|
Sign up to set email alerts
|

Undulation of W/matrix interface by resintering of cyclically heat-treated W-Ni-Fe heavy alloys

Abstract: When liquid-phase-sintered W-Ni-Fe alloys were cyclically heat treated at 1100 ЊC and resintered at 1485 ЊC, undulation of W/matrix interface resulted. The irregularity of the interface increased with the number of heat-treatment cycles. The residual thermal stress of W grains measured by X-ray diffraction increased with the number of heat-treatment cycles and exceeded the yield stress of W single crystal in certain crystallographic directions. A calculation by the finite element method (FEM) also showed nonun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
4
9
0
Order By: Relevance
“…Loading can be applied at a steady speed of about processing. [18,29] Particularly, in D specimen fabricated with 30 m/min using a speed reducer and step motors connected repeated sintering of 20 times, particles are sized up to about 75 m with their shape getting extremely irregular ( Figure 1(g)). Comparing the irregularity in A-R, B-R, and C-R Table I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loading can be applied at a steady speed of about processing. [18,29] Particularly, in D specimen fabricated with 30 m/min using a speed reducer and step motors connected repeated sintering of 20 times, particles are sized up to about 75 m with their shape getting extremely irregular ( Figure 1(g)). Comparing the irregularity in A-R, B-R, and C-R Table I.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, homogethose under repeated sintering are changed to irregularly neous deformation will give way to a localized bandlike shaped from spheroidal. [18] Dynamic torsional tests were deformation mode. This is an adiabatic shear band.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some studies reporting that such an irregular morphology is also observed in the cases of repeated heat treatment after sintering, or of resintering after deformation processing [14,22]. Particularly, in the D specimen fabricated with repeated sintering of 20 times, particles are sized up to about 75 Bm with their shape becoming extremely irregular.…”
Section: Microstructurementioning
confidence: 97%
“…This indicates that hardness of particles has a tendency to rise as particles become larger as a result of increasing the number, time, and temperature of sintering, although matrix hardness is almost the same, irrespective of repeated sintering. This can be explained by the formation of interfaces inside tungsten particles caused by the increased number of resinterings [14]. Rockwell hardness, which means overall bulk hardness, descends in the order of the A-S, B-S, and C-S specimens as sintering time becomes longer, and resintered A-R, B-R, and C-R specimens show slightly higher hardness over the A-S, B-S, and C-S specimens.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation